Design, analysis and validation of left ventricular assist device. (2021) - Antony, Martin; Tom, Melvin; Varghese, Jacob; Joseph, Sebin; Polachan, Sheen
Abstract: A left ventricular assist device is used in conditions where the patient is suffering from end-stage heart failure. LVAD is surgically implanted which helps the left ventricle to pump. Hemolysis is the major complication that occurs during the usage of this device. Hemolysis is the rupturing of red blood cells (RBCs). The shear stress developed in the pump and the exposure time of RBCs to these stresses is primarily responsible for the rupturing of red blood cells. In this project, a Centrifugal pump is developed and analyzed. Centrifugal pumps have a great advantage of high efficiency on par with reduced cost and simplicity. Computational modelling of the pump is done in ANSYS Software (CFx-Pre) using the Finite Difference Method (FDM). The corresponding shear stress field is found by solving transport equations for velocity components. Using the obtained shear stress value, the hemolysis index is calculated and verified using similar studies from published journals. The difficulties of using a centrifugal pump as an LVAD result from the use of blood as the working fluid. Hemolysis occurs as blood passes through the pump housing, and thrombi form in the low-velocity areas at the impeller bottom. Both of these phenomena are due to the working fluid's characteristics in the various flow fields induced in the pump.